LEXICAL-SEMANTIC STRUCTURE AND NATIONAL-CULTURAL ASPECT OF SPANISH AND UZBEK PHRASEOLOGISMS EXPRESSING SOME BASIC EMOTIONS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Phraseology is the branch of science that studies stable units that represent the objects of the human inner world more fully than lexemes. This study reveals the lexical-semantic structure and national cultural aspects of Spanish and Uzbek phraseological units that express basic emotions. The presented findings could serve as a basis for further studies aimed at identifying the mechanisms responsible for the lingua-cultural aspects of phraseological units.